(3GdCOhGJ GdeNJUI aj GdbQBf GdcQje (B:s (3JUfja LOjO ddCOhGJ HMSH GdGNJUGU hQUO JQGcjHgG aj GdbQBf GdcQje (B/s - (3NdGa, SjO eMeO SjOs ((3GdbGgQI (B:s (3YGde GdcJH,s, 2020)
(3ef CLd Pdc NWjH GdCOhGJ hGdMQha HCgJeGe GdfMGI hGddZhjf aj GdbOje hGdMOjK ; acKQJ eDdaGJge ajgG hPgHJ aj ePGgH GdJUfja cd ePgH fMhjG hOdGdjG heYLejG, EdG Cf JUfjaG hQO aj cJGHI SjHhjg de jfd ef GdYfGjI dOi GdeJCNQjf hGdeMOKjf eG fGdJg GdNWW GdJUfjajI GdCNQi, Pdc GdJUfja HMSH GNJUGU GdCOGI, hjCJj gPG GdcJGH ajbOe JUfjaG cGedG ddCOhGJ jbhe Ydi JLQjO GdSeGJ GdYGeI hGdNGUI ddGNJUGU aj SeGJ YOOjI, hJQJjHgG HMSH MXgG ef gPg GdSeGJ JQJjHG JUGYOjG(B.s
(3HHdjhLQGajI (B: (3UaMI (B343-352.s
Keywords: (3GdbQBfs -- (3dZI GdYQHjIs -- (3fMh hUQas